Behavioural Intent of Indian Consumers to Accept Mobile Banking Services - Khalid, Bushra; Sheerin, Aalia (South Asian Journal of Social Sciences and Humanities, 2020)
Banking system around the globe is becoming digitally advanced and India, too, has adopted the digital mode to transform the payment and settlement system. The number of mobile internet users is continuously increasing owing to the easy accessibility of mobile phones and cost efficiency of their usage. Mobile banking allows the consumers to conduct the financial transactions and other banking activities using mobile phones. Mobile banking has ensured easy and rapid accessibility of banking facility 24*7 and served as a medium to reach the unbanked, thereby becoming a gateway to financial inclusion. Digital innovations are critical for achieving and sustaining an inclusive economic growth, hence, eliminating poverty. In this paper, we have applied the extended version of the Technology Acceptance Model (TAM), originally given by Davis in 1989, to study the key determinants of behavioral intent of consumers to accept mobile banking services. TAM in itself is an adaptation of the Theory of Reasoned Action (TRA) (Fishbien and Ajzen, 1975). According to TRA, the actual action of an individual is determined by his/her behavioral intention, which, in turn, is influenced by his/her attitude and subject norm. The key constructs that have been studied in this paper are perceived ease-of-use, perceived usefulness, perceived credibility, normative pressures, self-efficacy and attitude to use. In order to achieve the objective, we have adapted a five-point Likert scale questionnaire containing 20items.The behavioral intent was then regressed against these key constructs. The study attempts to trace the causality between the behavioral intent and the main key constructs of TAM.